2007
DOI: 10.1128/jb.01896-06
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the First Genome of a Hyperthermophilic Marine Virus-Like Particle, PAV1, Isolated fromPyrococcus abyssi

Abstract: Only one virus-like particle (VLP) has been reported from hyperthermophilic Euryarchaeotes. This VLP, named PAV1, is shaped like a lemon and was isolated from a strain of "Pyrococcus abyssi," a deep-sea isolate. Its genome consists of a double-stranded circular DNA of 18 kb which is also present at a high copy number (60 per chromosome) free within the host cytoplasm but is not integrated into the host chromosome. Here, we report the results of complete analysis of the PAV1 genome. All the 25 predicted genes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 58 publications
1
53
0
Order By: Relevance
“…Marine archaea numerically dominate the mesopelagic oceans (Karner et al, 2001), with increased abundance in some surface waters (for example, the Southern Ocean; DeLong et al, 1994), yet their viruses are represented by a single isolate-a lemon-shaped virus from a hydrothermal deep-sea environment that infects Pyrococcus abyssi (Geslin et al, 2007). We observed no lemon-shaped viruses nor any of the myriad 'exceptional' morphotypes isolated from archaeal extremophiles (reviewed by Prangishvili et al, 2006).…”
Section: Discussionmentioning
confidence: 87%
“…Marine archaea numerically dominate the mesopelagic oceans (Karner et al, 2001), with increased abundance in some surface waters (for example, the Southern Ocean; DeLong et al, 1994), yet their viruses are represented by a single isolate-a lemon-shaped virus from a hydrothermal deep-sea environment that infects Pyrococcus abyssi (Geslin et al, 2007). We observed no lemon-shaped viruses nor any of the myriad 'exceptional' morphotypes isolated from archaeal extremophiles (reviewed by Prangishvili et al, 2006).…”
Section: Discussionmentioning
confidence: 87%
“…The circular dsDNA genome of PAV1 did not show similarity to other archaeal spindle-shaped viruses or, indeed, to any known virus (90). However, PAV1 shares several genes with plasmids from the Thermococcales (3 genes with Thermococcus nautilus plasmid pTN2 and an additional gene with Pyrococcus sp.…”
Section: Euryarchaeal Virusesmentioning
confidence: 99%
“…For example, APSV1 encodes four other proteins with homologues in tailless spindle- shaped viruses, including the DnaA-like AAA ϩ ATPase believed to be involved in genome replication (45). Similarly, in addition to the MCP, PAV1 shares a three-gene cassette with A3-VLP (23,46), while with TPV1, it shares two other genes for putative minor structural proteins (3). Notably, our analysis has shown that all spindle-shaped viruses encode AAA ϩ ATPases.…”
mentioning
confidence: 99%
“…Over the years, a number of spindle-shaped viruses that could not be assigned to the existing taxa based on genome similarity have been isolated from phylogenetically distant archaeal lineages, including Thermococcales (Thermococcus prieurii virus 1 [TPV1] [3] and PAV1 [2,23] (22). We used this information to perform an in-depth genome analysis of all known unclassified spindle-shaped viruses.…”
mentioning
confidence: 99%